Conceptualizing and Contextualizing Treatment Orientation: a Mixed-Method Analysis of Juvenile Correctional Staff under a Therapeutic Model - Brubaker, Sarah Jane (American journal of criminal justice, 2022)
Scholars have examined associations between treatment orientation and staff outcomes such as stress, burnout and turnover. However, existing operationalizations of treatment orientation are inconsistent, and the construct is often measured dichotomously, which fails to capture the complexity of staff experiences and perceptions. Our mixed method study of a newly implemented therapeutic program in a juvenile correctional facility identified multiple factors that contextualize staff support for the organization’s treatment orientation. First, an Exploratory Factor Analysis (EFA) of staff survey items identified factors that influenced support for the therapeutic model. Some staff liked particular features of the program, and some assessed its observed impact on resident behaviors and outcomes. Staff support was constrained by their perceptions of how the program was implemented, including the speed and consistency of implementation and adequacy of staffing. Both staff support for the program and perceptions of effective program implementation were related to supervisor support. Second, qualitative analysis of data from focus groups with staff illuminated preferences for a particular treatment orientation. Staff described how attempts to separate treatment from security in implementing a therapeutic approach both failed to provide a safe environment for residents and staff and contributed to role ambiguity and role conflict among staff. Staff also shared preferences for particular program components and perceptions that the therapeutic model was not appropriate for all residents, particularly those with blended sentences. The study’s findings have implications for future research, theory, and practice related to juvenile justice reform.